2001
DOI: 10.1039/b103594k
|View full text |Cite
|
Sign up to set email alerts
|

Selective ultra-trace detection of NO and NO2 in complex gas mixtures using broad-bandwidth REMPI mass spectrometry

Abstract: In this paper we demonstrate the feasibility of ultra-trace resonance enhanced multiphoton ionization (REMPI) detection employing a small broad-bandwidth solid state laser system. The results reported here are compared with measurements carried out with a conventional excimer pumped dye laser combination. Mass selected broad-bandwidth REMPI spectra for the environmentally relevant nitrogen oxides NO and NO2 are presented. Tunable broad-bandwidth laser radiation with a spectral resolution of > 10 cm(-1) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 35 publications
1
26
1
Order By: Relevance
“…Results reported in a recent paper are promising [30]. It is shown that under limited rotational cooling conditions the efficiency of selected photo ionization processes in conjunction with broad-bandwidth laser excitation results in a similar performance with respect to sensitivity compared to the jet-cooling/narrow bandwidth excitation approach.…”
Section: Discussionsupporting
confidence: 50%
“…Results reported in a recent paper are promising [30]. It is shown that under limited rotational cooling conditions the efficiency of selected photo ionization processes in conjunction with broad-bandwidth laser excitation results in a similar performance with respect to sensitivity compared to the jet-cooling/narrow bandwidth excitation approach.…”
Section: Discussionsupporting
confidence: 50%
“…On the other hand, when d > 2, the resulting curves are overlapped, hence no improvement is achieved. It should be underlined that the high sensitivity attained just for small concentrations of reactants makes this analytic technique very suitable for the determination of ultratrace amounts of reactants, which is of great experimental importance [29,30,31] …”
Section: Simulationsmentioning
confidence: 99%
“…Both coils have similar dimension than the HONO/O3-scrubber. The gas phase is sucked with a membrane pump through the stripping-coils, a security flask with electrical control, a Teflon membrane HONO (Milani and Dasgupta, 2001) and ozone interferences (Adema, 1979) by the Griess-Saltzman reaction are suppressed. NO 2 and other potential interferences are collected in the second stripping-coil (Channel 1), while potential interferences are measured in the third coil (Channel 2).…”
Section: Sampling Unitmentioning
confidence: 99%
“…Spectroscopic methods such as Differential Optical Absorption Spectroscopy (DOAS) (Platt et al, 1979;Edner et al, 1993;Thornton et al, 2003), Laser Induced Fluorescence (LIF) (Thornton et al, 2000;Matsumoto et al, 2001Matsumoto et al, , 2006Dari-Salisburgo et al, 2009;Fuchs et al, 2010), Cavity Ring Down Spectroscopy (CRDS) (Mazurenka et al, 2003;Hargrove et al, 2006;Osthoff et al, 2006;Fuchs et al, 2009Fuchs et al, , 2010, Incoherent Broad Band Cavity Enhanced Absorption Spectroscopy (IBBCEAS) (Gherman et al, 2008;Wu et al, 2009;Fuchs et al, 2010), Cavity Attenuated Phase shift Spectroscopy (CAPS) (Kebabian et al, 2005(Kebabian et al, , 2008, Tunable Diode Laser Absorption Spectroscopy (TDLAS) (Gregory et al, 1990;Li et al, 2004;Herndon et al, 2004), and Resonance Enhanced MultiPhoton Ionization (REMPI) (Garnica et al, 2000;McKeachie et al, 2001) have been used for NO 2 detection, with some of them reaching very low detections limits (e.g. REMPI, LIF).…”
Section: Introductionmentioning
confidence: 99%